Design of shuffling protocol based on additive secret sharing - ZHANG Yanshuo; MAN Ziqi; ZHOU Xingyu; YANG Yatao; HU Ronglei (Tongxin xuebao)
Aiming at the problems such as lack of specific algorithms for process implementation, using public keys in most of the solutions, low efficiency in dealing with large-scale data sets, and lack of applicability, a unilateral shuffling protocol was proposed, and on this basis, a shuffling protocol based on additive secret sharing was designed. The share conversion algorithm was constructed through the casual transfer protocol, and the shuffling was completed without exposing the original data set. The shuffling task was decomposed into multiple sub-tasks by the Benes arrangement network, which improved the efficiency of large-scale data sets. Finally, through the additive secret sharing, the shuffling shares were safely distributed to the participants. The correctness of the proposed shuffling protocol was analyzed strictly, and its security property was evaluated by using an ideal-reality simulation paradigm. Compared with the existing literature, the proposed protocol can meet the current security standards in security, and has high efficiency in processing large-scale data sets. It improves the applicability of the protocol and further promotes its application in the current environment.